Experimental studies of the characteristics of a lidar emitter based on a pump-dye laser - Zarudyi А.А. (Radiotekhnika, 2018)
The results of experimental studies of the flashlamp pumped organic dye laser with a dispersion resonator are presented. Intracavity interferometers were used for narrowing the spectrum and tuning the radiation frequency. The results of the studies indicate that there is an optimal value for the length of the active element, at which the maximum spectral brightness of the radiation is realized.